2021
DOI: 10.3389/fimmu.2021.676932
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of COVID-19 Patients Shows Age-Associated T Cell Changes Independent of Ongoing Ill-Health

Abstract: ObjectivesThe immunological and inflammatory changes following acute COVID-19 are hugely variable. Persistent clinical symptoms following resolution of initial infection, termed long COVID, are also hugely variable, but association with immunological changes has not been described. We investigate changing immunological parameters in convalescent COVID-19 and interrogate their potential relationships with persistent symptoms.MethodsWe performed paired immunophenotyping at initial SARS-CoV-2 infection and conval… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 67 publications
3
38
1
Order By: Relevance
“…Our group and others have observed T cell activation that persists into the early convalescent phase following SARS-CoV-2 infection ( 1 , 8 ), but few studies have investigated phenotypic differences into the intermediate and late phases of convalescence, particularly in individuals with prolonged symptom syndromes. One recent study observed longitudinal changes in T cell activation independent of ongoing symptoms ( 9 ). To investigate T cell changes in our cohort, we first characterized T cell activation as determined by dual expression of HLA-DR and CD38, previously shown to be upregulated in severely infected COVID-19 patients ( 2 ), and found that the CD4 + T cell population had increased HLA-DR + CD38 + expression when comparing early and intermediate time points, as well as when comparing the early time point with CoV – controls ( Figure 2A ; P = 0.024 and P = 0.021, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group and others have observed T cell activation that persists into the early convalescent phase following SARS-CoV-2 infection ( 1 , 8 ), but few studies have investigated phenotypic differences into the intermediate and late phases of convalescence, particularly in individuals with prolonged symptom syndromes. One recent study observed longitudinal changes in T cell activation independent of ongoing symptoms ( 9 ). To investigate T cell changes in our cohort, we first characterized T cell activation as determined by dual expression of HLA-DR and CD38, previously shown to be upregulated in severely infected COVID-19 patients ( 2 ), and found that the CD4 + T cell population had increased HLA-DR + CD38 + expression when comparing early and intermediate time points, as well as when comparing the early time point with CoV – controls ( Figure 2A ; P = 0.024 and P = 0.021, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Our group and others have characterized the acute immune response to COVID-19, finding dramatic immune dysregulation in peripheral blood samples from infected individuals ( 1 7 ), especially in those with severe infection. Evidence suggests some of these immune perturbations persist into the convalescent phase of infection ( 1 , 8 , 9 ). Antigen-specific immune responses during the acute and early convalescent stages of infection have been found to play an important role in overall patient outcomes ( 10 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study examined vitamin D levels during initial infection in hospitalised patients and persistent symptoms at eight weeks post illness and also found no relationship [ 61 ]. The lack of associations seen emphasise that long COVID remains a symptom-driven disease, with no reliable or reproducible biomarker [ 62 , 63 ]. This is also reflected in the levels of CRP and IL-6 recorded, with the majority being within normal range.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any differences in natural killer (NK) cell subpopulations, except for decreased terminal NK cells in PSP compared with NSP ( p < 0.05) that recovered after treatment ( p < 0.01, Figure S1 ). Within the monocyte compartment, there was a trend towards overrepresentation of intermediate monocytes (CD14+CD16+) in PSP, as observed during acute COVID-19 [ 18 , 19 , 20 ], while classical (CD14+CD16−) and non-classical (CD14−CD16+) monocytes showed similar levels to NSP ( Figure S2a ). The surface expression of CCR2, CCR5, HLA-DR, and CD86 in the non-inflammatory, classical monocytes was similar between NSP and PSP ( Figure S2b ).…”
Section: Resultsmentioning
confidence: 65%
“…All NSP and PSP included in the study had a current negative antigen test and RT-PCR for SARS-CoV-2 from nasopharyngeal samples; however, this does not exclude the possibility of viral persistence in other locations such as central nervous or digestive systems [ 24 , 25 , 26 ]. Alterations in the T cell compartment have been described in convalescent COVID-19 patients, particularly the persistence of activated CD8+ T cells for up to 6 months post-infection [ 19 , 27 ]. Despite the aforementioned disturbances in the distribution of T cell populations, the secretion of interleukin (IL)-2, interferon gamma (IFNg), and tumor necrosis factor alpha (TNFa) by CD4+ or CD8+ T cells after polyclonal in vitro stimulation was similar between PSP and NSP, and corticosteroid treatment did not have a clear effect on cytokine synthesis ( Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%